Circular dichroism studies of an oligo-alpha-thymidylate and of its interactions with complementary sequences. - Durand, M (1988)
An octathymidylate synthesized with the alpha anomer of thymidine has been studied using circular dichroism. Its conformation has been compared to that of its analogue containing the naturally occurring beta anomer. In both compounds some degree of intramolecular stacking is present as indicated by the shapes of the circular dichroism spectra and their variations with temperature. As its beta-analogue the alpha-octathymidylate binds to its complementary sequences containing beta-nucleosides. Only complexes with 1A:1T stoechiometry were observed. Binding to ribose- containing oligomers and polymers is much stronger than binding to deoxyribose-containing analogues. Circular dichroism spectra provided evidence for a difference between the geometry of the various complexes formed with an alpha-oligothymidylate and those formed with its beta-anomer-containing analogue.